Is mastectomy oncologically safer than breast-conserving treatment in early breast cancer - Riedel, Fabian; Hennigs, André; Fastner, Sarah; Schäfgen, Benedikt; Sohn, Christof; Schütz, Florian; Golatta, Michael; Heil, Jörg (Breast care, 2017)
To describe and discuss the evidence for oncological safety of different procedures in oncological breast surgery, i.e. breast-conserving treatment versus mastectomy. Methods: Literature review and discussion. Results: Oncological safety in breast cancer surgery has many dimensions. Breast-conserving treatment has been established as the standard surgical procedure for primary breast cancer and fits to the preferences of most breast cancer patients concerning oncological safety and aesthetic outcome. Conclusions: Breast-conserving treatment is safe. Nonetheless, the preferences of the individual patients in their consideration of breast conservation versus mastectomy should be integrated into routine treatment decisions.